Succession Planning in a Family Owned Hotel Business - Patel, Mitesh; Patel, Ritesh; Patel, Nikunj (Prabandhan: Indian Journal of Management, 2019)
Evolving markets in Asia are unseating the epicentre of new hospitality investments and are switching their focus to India. The Indian economy is the seventh largest economy in the world as per the nominal GDP, and third largest as per the purchasing power parity. Gujarat is one of the growing states of India where many small businesses are operating. India’s growing income and concept of small family businesses continue to support domestic and international tourism that boost the hotel industry in India. This case study was an attempt to provide strategic orientation to students for succession planning in business and to equip students with challenges while doing business. This case study is of a small business, which grew successfully by means of the effective use of succession planning. The potential audience of this case are the students of MBA, PGDM course, and management programmes. This case study is also important for small and medium sized enterprises. The case explained the key success factors, key competitors with their strategies, strategies of Natraj Hotel to handle competitors, succession planning for next generation, and expected future challenges.